Biological characteristics of lacewing larvae chrysoperla carnea feeding on cotton white fly numphs bemisia tabaci in laboratory condition (Journal of Hama University, 2024)
This study was conducted to evaluate the efficiency of the predator C. carnea (native strain in the middle region of Syria) and to study some life characteristics of it when feeding on white fly Bemisia tabaci nymphs. The experiment was carried out under normal laboratory conditions; temperature ranging between 19 and 25° C during the period of presence of B. tabaci in the cotton field. All predator larvae instars were fed on the third and fourth numphs instar of B. tabaci. The larval development period of the predator was 19.88 days, and the average periods of the three larval instars of the predator were 5.71, 5.47, and 8.71 days, respectively. The average number of whitefly nymphs consumed by each larva was 415 numphs, and the numbers of preyes consumed by each larval instar were 25.24, 55.27, and 335.50 nymphs, respectively. The average daily consumption of the first, second and third larval instar were 4.29 and 10.27 and 45.40 whitefly nymphs/day, respectively. The lowest survival rate of larvae was 42.5% at the end of the first instar , while the survival rate at the end of the second instar was 88.24%, the highest survival rate was 93.33% at the end of the third instar, and the survival rate of predator individuals at the end of the larval stage was 35%.